A coalition-driven examination of organization capacity to address food insecurity in Greater Houston: a qualitative research study - John, Jemima C.; Gonzalez, Jennifer; Chan, Sara-Grace; McPherson, Heidi; Aiyer, Jennifer N.; Galvan, Esperanza; Browning, Nicole; Sharma, Shreela V. (Frontiers in Public Health, 2023)
Background: Economic and social hardships have worsened food insecurity, particularly among low income and racial-ethnic minority groups. Given the core goal of the 150+ member Houston Health Equity Collective (HEC) to reduce food insecurity by 5% in 2025, we explored member organizations’ capacity and challenges faced in screening and responding to food insecurity through care coordination efforts. Methods: A twice-administered Qualtrics XM survey (Provo, Utah) with 76 organizations, followed by five focus groups with 22 of these organizations, explored reach and response efforts to food insecurity. Qualitative assessments lasted between 0.5 to 1.5 hours, were audio-recorded, cleaned, coded, and thematically analyzed using NVivo, version 11 (Burlington, Massachusetts). The qualitative study was guided by a general inductive approach. In total, over six hours of audiovisual recording was extracted, and over 100 pages of text exported to NVivo for data analysis. The research team read and coded transcripts independently using the codebook, and met routinely to discuss and resolve codes -resulting in numerous revisions to the codebook. Coding structure was discussed at multiple meetings and differences were addressed through consensus. Predominant qualitative themes impacting food insecurity screening were “stigma and cultural-related barriers”, “clinic capacity and attitudes”, “need to focus on upstream influences of food insecurity and SDOH needs”, “impact of COVID-19”, and "need for HEC system responses". Main recommendations to enhance screening and reach included improving staff culture, enhancing cultural sensitivity across organizational practices, and using shared technology to coordinate care. Respondents stated that the HEC can drive these recommendations through networking opportunities, use of shared resource directory, and placing focus on upstream factors. Conclusions: Recommendations to target food insecurity must focus on organizational staff responsiveness and sensitivity to patients’ needs. Of equal importance is the need for increased attention to the upstream influencers and integration of systems-level interventions to holistically target the barriers impacting food insecurity.